Effects of Telmisartan with Hydrochlorothiazide versus Valsartan with Hydrochlorothiazide in Patients with Moderate-to-Severe Hypertension - Ravi Marfatia; William B. White; Helmut Schumacher (International Journal of Hypertension)
Combination therapy is recommended for patients with blood pressure (BP) significantly above goal by recent consensus guidelines around the globe. The use of angiotensin II receptor blockers (ARBs) alone or in combination with a thiazide diuretic is a preferred treatment strategy due to both efficacy and safety considerations. However, there are few data known about the benefits of ARB-diuretic combination therapy in patients with moderate-to-severe hypertension. We performed a subanalysis from two large clinical trials that compared the antihypertensive effects of telmisartan 80 mg versus valsartan 160 mg, both combined with hydrochlorothiazide (HCTZ) 25 mg in a subpopulation of 725 patients with moderate-to-severe hypertension (systolic BP SBP ≥ 160 mm Hg). Treatment with telmisartan-HCTZ induced significantly greater reductions in BP (−31.1/−18.3 mm Hg) than valsartan-HCTZ (−28.4/−16.3 mm Hg; SBP 𝑃=0.0265, diastolic BP 𝑃=0.0041). More patients receiving the telmisartan combination achieved a BP goal < 140/90 mm Hg than those receiving valsartan-HCTZ. There were similar safety and tolerability data for the two active treatment groups. These findings support the use of longer-acting ARBs combined with higher doses of thiazide diuretic to improve BP control in patients with moderate-to-severe hypertension.